NUTRIENT CONTENT OF SERICULTURE WASTE SUPPLEMENTED VERMICOMPOST BY PERIONYX EXCAVATUS - MAMATA PANDEY; T. V. RAO; S. K. SATAPATHY (The Bioscan, 2010)
Besides silk production sericulture industry also produces large amount of waste which goes unutilized. This organic waste can be profitably utilized for vermicomposting which has a lot of market potential. The present work is intended to investigate the quality of the compost of the sericulture waste produces through vermicomposting. Composting of the waste was done with Perionyx excavatus, a locally available epigeic earthworm. During 60 days of the decomposition, nutrients such as organic carbon, available nitrogen, potassium, sodium, and phosphorus were analyzed. Quality of the compost on 0,15,30,45, and 60 days of decomposition depicted that C and, C/N ratio were decreased. On the other hand the content of N, K, Na and P were significantly increased (p d” 0.05) during the period of decomposition. The study infers that the waste from sericulture provides better quality compost in comparison with that prepared from only cow dung.